Rethinking Tarkam Football Competition as A Complexity of Social Entrepreneurship Practice in Rural Indonesia - Kusmulyono, Muhammad Setiawan; Ahmad, Faizal; Permana, Yogie; Jayawardhana, Irman (Sodality: Jurnal Sosiologi Pedesaan, 2025)
Football is the supreme sport in Indonesia. This popularity arises from football being a sport accessible to the crowds, easy to get involved in, and requiring minimal money to play. Football is more engaging when contested in a competitive league system. In Indonesia, there are both professional leagues run by football federations and grassroots championships known as Tarkam (antar-kampung / inter-village) tournaments conducted in rural regions. The Tarkam competition encompasses numerous traditions and includes up to 17 actors in the Tarkam football stakeholder mapping. This study employs an exploratory methodology, gathering data via content analysis and interviews with Tarkam football participants to elucidate the dynamics of football inside Tarkam. This study investigates the possibilities of social entrepreneurship in the execution of Tarkam tournaments. This study aims to unveil an alternative perspective of the Tarkam phenomenon, highlighting that it transcends just the sporting and economic dimensions. The study’s findings indicate that the execution of Tarkam tournaments aligns with the principles of social entrepreneurship, albeit in a more intricate manner; yet, certain social issues remain unaddressed within the existing tarkam framework.